Pola Asuh Orang Tua dalam Menumbuhkan Spiritualitas Anak di Jemaat GMIM Imanuel Taratara - Clara Inri Rumajar; Semuel Selanno; Art Thomas (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to examine the parenting pattern of parents in growing children's spirituality in the GMIM Imanuel Taratara Congregation, analyze the factors that influence parenting patterns in growing children's spirituality in the GMIM Imanuel Taratara Congregation and describes the efforts made to overcome obstacles in parenting patterns in growing children's spirituality in the GMIM Imanuel Taratara Congregation. The researcher used a descriptive qualitative research method which was carried out at the GMIM Imanuel Taratara Congregation. From the results of data exposure, findings and discussion, it is necessary for parents to understand the importance of parenting in fostering children's spirituality so that they can direct children to be able to grow spirituality well.